2023
DOI: 10.1007/s00127-023-02484-2
|View full text |Cite|
|
Sign up to set email alerts
|

Risk of suicide and self-harm in university students entering different university programs – a national register-based cohort study in Sweden

Abstract: Purpose It is not known whether the elevated suicide risk in certain occupations, such as health care professionals, is partly attributable to a selection of individuals with prior vulnerability. We aimed to determine the risk of suicide and self-harm already in students entering different university programs. Methods We used national registers to identify 621,218 Swedish residents aged 18–39 years with registration for a university program 1993–2013. Outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Some nurses may possess a predisposition to suicide which precedes their nursing career, for example, childhood trauma, or a family history of mental illness or suicide.Financialdifficultiesarecommonamongnursesandstudentnursesandadditionalpsychosocialadversitysuchashousing problems or relationship difficulties might increase vulnerability. Alargeproportionofnurseswhodiebysuicideareknowntohave a history of mental health problems and/or self-harm (Groves etal.,2023),whichmaypredateentryintonursing.Arecentstudy inSwedenfoundthatfemalestudentnurseswereatincreasedrisk ofsuicideandself-harmcomparedtostudentsofotherdisciplines, but this elevated risk dissipated when hospitalization for mental illness prior to entering training was controlled for (Lageborn et al, 2023), therefore suggesting vulnerability was present be-…”
Section: Why Are N Ur S E S At Ris K Of Suicide?mentioning
confidence: 99%
See 1 more Smart Citation
“…Some nurses may possess a predisposition to suicide which precedes their nursing career, for example, childhood trauma, or a family history of mental illness or suicide.Financialdifficultiesarecommonamongnursesandstudentnursesandadditionalpsychosocialadversitysuchashousing problems or relationship difficulties might increase vulnerability. Alargeproportionofnurseswhodiebysuicideareknowntohave a history of mental health problems and/or self-harm (Groves etal.,2023),whichmaypredateentryintonursing.Arecentstudy inSwedenfoundthatfemalestudentnurseswereatincreasedrisk ofsuicideandself-harmcomparedtostudentsofotherdisciplines, but this elevated risk dissipated when hospitalization for mental illness prior to entering training was controlled for (Lageborn et al, 2023), therefore suggesting vulnerability was present be-…”
Section: Why Are N Ur S E S At Ris K Of Suicide?mentioning
confidence: 99%
“…A large proportion of nurses who die by suicide are known to have a history of mental health problems and/or self‐harm (Groves et al., 2023), which may predate entry into nursing. A recent study in Sweden found that female student nurses were at increased risk of suicide and self‐harm compared to students of other disciplines, but this elevated risk dissipated when hospitalization for mental illness prior to entering training was controlled for (Lageborn et al., 2023), therefore suggesting vulnerability was present before entering nursing training.…”
Section: Why Are Nurses At Risk Of Suicide?mentioning
confidence: 99%
“…One study in Sweden examined suicide risk among nursing students using a national cohort study (Lageborn et al, 2023). Female nursing students had increased risk of suicide compared to a reference group of education students, including after adjustment for age and calendar year (OR: 2.4 (1.0-5.8)).…”
Section: Suicidementioning
confidence: 99%
“…Five studies examined self-harm (Heath et al, 2021;Lageborn et al, 2023;Mao et al, 2021;Ramluggun et al, 2018;Safira et al, 2022). Self-harm methods were not described.…”
Section: Self-harmmentioning
confidence: 99%